A dynamic thiol-disulfide exchange assisted high cell-penetrating fluorescent probe for intracellular H2S detection. (November 2022) - Feng, Gang; Li, Zhengzheng; Zhang, Xinmeng; Huang, Haoqiang; Zhai, Peng; Jiang, Yihang; Fan, Miaozhuang; Xu, Zhourui; Wang, Xiaomei; Ying, Ming; Yang, Chengbin; Dong, Biqin; et al.
Abstract: Hydrogen sulfide (H2 S) is a gaseous signaling transmitter which plays a crucial role in cell fates. Given the volatility of H2 S in live cells corresponding to the various cell activities, it is important to design and synthesize novel fluorescent probes which could enter cells rapidly for the fast H2 S detection. Herein, we reported a turn-on fluorescent probe P1 for H2 S labeling in live cells, based on the dynamic thiol-disulfide exchange mechanism on cell surface, which facilitated the probe to enter cells quickly. High performance liquid chromatography (HPLC) results indicated the decoration of cell-penetrating disulfides endowed P1 with a high cellular uptake efficiency. Fluorescence microscopic imaging for HeLa cells suggested P1 was competent for intracellular H2 S detection at submicromolar level. We expected our simple but effect strategy which enhanced the cell permeability of probes to benefit more accurate detection for intracellular specific molecule. Graphical abstract: (a) The enhanced cellular permeability of fluorescent probe P1 was achieved by the passive diffusion (black arrow) and the dynamic thiol-disulfide exchange on cell surfaces (red arrows); (b) Fluorescent response of fluorescent probe P1 toward H2 S. Image 1 Highlights: Fluorescent probe P1 was developed based on the dynamic thiol-disulfide exchange mechanism. HPLC results confirmed the enhanced cell permeability of probe P1. Probe P1 possessed excellent fluorescent performance with a large Stokes shift (110 nm). The selectivity and sensitivity toward H2 S of probe P1 were good. H2 S detection was performed by the probe in live cells.